FATTY ACID PROFILES IN FISH SILAGE MADE FROM VARIOUS MARINE FEEDSTUFFS AS POTENTIAL NUTRITION SOURCES FOR AQUACULTURE FEEDS - Agung Sudaryono (JOURNAL OF COASTAL DEVELOPMENT, 2005)
This study was designed to evaluate fish silage made from various marine feedstuffs (shrimp head, blue crab waste, mud crab waste, squid and tigawaja trash fish) as potential sources of n-3 fatty acids for aquaculture feeds. The marine feedstuffs and the fish silage were analysed for fatty acids contents. Results of fatty acid analysis showed that all the fish silage had higher levels of PUFA (polyunsaturated fatty acid) of linolenic acid (LNA; 18:3n-3) and HUFA (highly unsaturated fatty acid) of eicosapentaenoic acid (EPA; 20:5n-3) and docosahexaenoic acid (DHA; 22:6n-3) than the feedstuffs. This study indicates that the bioactive substances contents of n-3 fatty acids (LNA, EPA, DHA) in squid can be significantly improved by manufacturing the fish silage. Fish silage from squid was found to be the most potential source for PUFA (LNA; 5.08 vs 10.72) and HUFA (EPA; 8.07 vs 17.50 and DHA; 7.18 vs 18.08 g/100 g lipid) among the others and suitable for aquaculture feeds.